221k views
2 votes
Henry correctly subtracted 3p+5/3p from 4p+3/p-2 and got 12p2+9p-3p2+p10/(p-2)(3p). What is the simplified difference?

User Calcolat
by
5.9k points

1 Answer

6 votes

Answer:

Simplified expression is
(9p^(2)+10p+10)/(3p(p-2))

Explanation:

In this question the two fractions are
(4p+3)/(p-2) and
(3p+5)/(3p)

Now Henry subtracts first fraction from the second.


=(4p+3)/(p-2)-(3p+5)/(3p)


=((4p+3)3p-(3p+5)(p-2))/(3p(p-2))


=(12p^(2)+9p-(3p^(2)+5p-6p-10))/(3p(p-2))


=(12p^(2)+9p-3p^(2)+p+10)/(3p(p-2))


=(9p^(2)+10p+10)/(3p(p-2))

So the simplified difference is
(9p^(2)+10p+10)/(3p(p-2))

User Alex Amato
by
6.0k points